2019
DOI: 10.1016/j.jeem.2019.02.001
|View full text |Cite
|
Sign up to set email alerts
|

CEO education and corporate environmental footprint

Abstract: This version of the article has been accepted for publication and undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process, which may lead to differences between this version and the publisher's final version AKA Version of Record.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
65
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 107 publications
(74 citation statements)
references
References 69 publications
6
65
0
3
Order By: Relevance
“…Similarly, Lewis et al (2014) found that managers, who held MBA degrees, tend to publish environmental information whereas, colleagues, who held law degrees, are less likely to publish this type of information than other businesses. In the same vein, Amore et al (2019) presented a positive relationship between CEO education and CEP. There are several empirical studies that provide evidence to explain why better-educated CEOs usually lead to better environmental performance.…”
Section: Ceo Educationmentioning
confidence: 84%
See 1 more Smart Citation
“…Similarly, Lewis et al (2014) found that managers, who held MBA degrees, tend to publish environmental information whereas, colleagues, who held law degrees, are less likely to publish this type of information than other businesses. In the same vein, Amore et al (2019) presented a positive relationship between CEO education and CEP. There are several empirical studies that provide evidence to explain why better-educated CEOs usually lead to better environmental performance.…”
Section: Ceo Educationmentioning
confidence: 84%
“…This finding verifies our third hypothesis (3a and 3b) which stats that there is a positive association between CEO education and the possibility of CEP, and is also consistent with the extant studies that illustrate that higher educated individuals tend to engage in a more environmentally friendly orientation (Meyer, 2015). Amore et al (2019) also suggested that education shapes managerial styles of CEOs in environment-related issues. Moreover, higher levels of CEOs' education level tend to be positively related to the levels of their knowledge about environmental responsibility issues.…”
Section: Discussionmentioning
confidence: 99%
“…As a future‐oriented investment, CER promotes the sustainable development of enterprises (Amore et al, 2019; Hart & Caggiano, 2003; He & Chen, 2009; Wang, 2010), which may improve companies' earnings persistence and investors' earnings response at the same time. This section discusses the literature in the field and proposes hypotheses accordingly.…”
Section: Mechanism Analysis and Hypothesis Proposalmentioning
confidence: 99%
“…Moreover, higher operational efficiency is a source of competitive advantage (Boyer & Lewis, 2002; Day, 1994; Terjesena, Patelb, & Covin, 2011), which ultimately affects the accounting performance of enterprises (Yu, Ramanathan, & Nath, 2014). Specifically, first, CER usually relies on higher level tasks, which require changing the existing production mode and encouraging enterprises to adopt more environmentally friendly technologies (Amore et al, 2019; Shi & Xu, 2018; Tanaka, 2015; Wang, Hang, Su, & Zhou, 2018). According to Hart and Caggiano (2003), clean technology is a critical component of sustainable development.…”
Section: Mechanism Analysis and Hypothesis Proposalmentioning
confidence: 99%
See 1 more Smart Citation